2019
DOI: 10.1103/physrevphyseducres.15.010125
|View full text |Cite
|
Sign up to set email alerts
|

Content-specific pedagogical knowledge, practices, and beliefs underlying the design of physics lessons: A case study

Abstract: We present an analysis of the in situ support provided to preservice physics teachers (PPTs) enrolled in a Methods for Teaching Physics course (N ¼ 28) at a research university, while working on the design of 20 lessons in mechanics and waves they taught later in the course. The PPTs submitted 4 evolving plans for each lesson, and received guidance and support in two consecutive consultation meetings on each lesson plan (30 min each), as well as written feedback via the course website. Using grounded theory me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The present systems fall short and new and different teaching methods should be tried (Djudin, 2018). Kapon and Merzel (2019) also contend that teachers should be guided with such studies so that students and the field benefit from it. In this respect, in this action research, the researcher collaborated with the teacher; the teacher was never left alone, and she was facilitated to overcome problems.…”
Section: Discussionmentioning
confidence: 99%
“…The present systems fall short and new and different teaching methods should be tried (Djudin, 2018). Kapon and Merzel (2019) also contend that teachers should be guided with such studies so that students and the field benefit from it. In this respect, in this action research, the researcher collaborated with the teacher; the teacher was never left alone, and she was facilitated to overcome problems.…”
Section: Discussionmentioning
confidence: 99%
“…Two research questions guided the study reported in this paper: What instructional materials and activities can support university teaching to highlight the structural role of mathematics in the development of new ideas in physics, and overcome the tendency to reduce it to a mere technical instrument [1,[17][18][19][20]? What is the effect of these materials and activities on students' understanding, epistemologies and skill development?…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Although based on a case study, the paper has the ambition to contribute to the wider debate in physics education research about the role played by mathematics in physics teaching and learning, and the main research questions go beyond the specific case: What instructional materials, curricular choices, and activities can support university teaching to boost students to understand the authentic roles of mathematics in the development of new ideas in physics? In particular, we articulate the above question into two subquestions: What instructional materials and activities can support university teaching to highlight the structural role of mathematics in the development of new ideas in physics, and overcome the tendency to reduce it to a mere technical instrument [1,[17][18][19][20]? What is the effect of these materials and activities on students' understanding, epistemologies, and skills development?…”
Section: A the Case Of Blackbody And Beyondmentioning
confidence: 99%